Making preschool inclusion work strategies for supporting children, teachers, and programs - Richardson-Gibbs, Anne Marie; Klein, M. Diane (Baltimore Paul H. Brookes Publishing Co., 2014)
This comprehensive textbook gives education professionals a thorough introduction to inclusion supports: evidence-based practices and strategies that help children with disabilities fully participate in preschool classrooms. Practical materials: In-depth case studies and vignettes from both professional and parent perspectives, strategies for adapting curriculum content, disability-specific interventions to keep and use as a reference
About the Authors - Contributors - Foreword -- Acknowledgments -- An introduction to preschool inclusion support practices -- Models of inclusion support / Kathleen C. Harris, Ph.D. -- Getting started: administrative and leadership strategies for building inclusive preschool programs -- Preparing for the individualized education program and working with families -- problem solving and conflict resolution -- Appendix 5A: two case studies / Jonny and Brandon -- Strategies that support the needs of all learners -- Disability-specific challenges and strategies in inclusive preschool programs / with invited contributors Beth A. Moore, M.A., Sue Parker-Strafaci, M.A., Sherwood J. Best, Ph.D., Sara Chen Ling, M.A., Janice Myck-Wayne, Ed.D., Jennifer Symon, Ph.D., BCBA-D, and Michelle Dean, Ph.D. -- Positive behavior supports: preventing and managing difficult behavior / Kathryn D. Peckham-Hardin, Ph.D. -- Preparing for kindergarten: adaptations and supports across the curriculum -- Index
Includes bibliographical references and index.
Keywords: Children with disabilities -- Education (Early childhood) -- United States; Inclusive education -- United States